O comportamento do consumidor de alimentos no contexto pós-pandemia - Souza, Júlia Campos (Universidade Federal de São Carlos, 2023)
The Covid-19 pandemic caused impacts around the world, interfering in the business models, social dynamics and the population's routine, especially in their eating habits. In addition to encouraging consumers to seek a healthier diet, thinking about strengthening the immune system against the virus, it reinforced guidelines and debates regarding food quality and safety, as well as care for the environment and brand principles. The food sector is constantly evolving to meet market demands, which can change quickly or remain traditional for a long period of time. For this reason, it is essential that companies keep up to date with the consumer profile and the factors that directly influence their purchase decision. With that in mind, this work aimed to collect responses from residents of Brazil and other regions of the world through online forms about consumer preferences in the post-pandemic context, gathering questions about diets, packaging, places of purchase, sales prices, organic and vegan products, and Food Security, to form a material rich in information on trends and market projections that may be useful for future innovation projects and research in the food area. The results were assembled into interactive dashboards in Microsoft Power BI and correlated with other recently published surveys. At the end of the analysis, it could be concluded that the pandemic scenario, indeed, brought significant changes to various food sectors and to the lives of the consuming public, who are increasingly critical in their choices, due to growing environmental concerns, greater attention to the principles and positioning of brands and interest in more natural and nutritious products. In addition, with the world still recovering from the effects of the pandemic, debates on food accessibility and availability are urgent to combat the high levels of food insecurity.
The food consumer behavior in the post-pandemic scenario
Keywords: Pandemia; Covid-19; Preferências do consumidor; Segurança alimentar; Pandemic; Covid-19; Consumer preferences; Food security; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::AVALIACAO E CONTROLE DE QUALIDADE DE ALIMENTOS